1998
DOI: 10.1038/sj.sc.3100698
|View full text |Cite
|
Sign up to set email alerts
|

Detraining from total body exercise ergometry in individuals with spinal cord injury

Abstract: This study was designed to investigate the e ects of detraining that occurred during an 8 week period of muscular inactivity following a 12 week training program of arti®cial computerized functional electrical stimulation cycle ergometry (CFES LE) and arm ergometry. Six spinal cord injured male individuals were followed through an 8 week detraining period that was preceded by a 12 week exercise program including CFES LE and arm ergometry. Maximal graded exercise tests were completed and measurements of peak ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…When FMS was discontinued for 4 weeks, these values had the following decrements: MIP (4.3%), IRV (6.0%), and PIF (5.4%); MEP (1.0%), ERV (4.0%), and PEF (8.1%) when compared with their maximal PFT measurements. This functional decrease was comparable with that reported by Gurney et al [32] and with findings from our previous expiratory muscle conditioning study [29], which showed decreased skeletal muscle performance after the cessation of training in SCI. This outcome suggests that continual FMS may be necessary to maintain improved inspiratory and expiratory functions.…”
Section: Discussionsupporting
confidence: 92%
“…When FMS was discontinued for 4 weeks, these values had the following decrements: MIP (4.3%), IRV (6.0%), and PIF (5.4%); MEP (1.0%), ERV (4.0%), and PEF (8.1%) when compared with their maximal PFT measurements. This functional decrease was comparable with that reported by Gurney et al [32] and with findings from our previous expiratory muscle conditioning study [29], which showed decreased skeletal muscle performance after the cessation of training in SCI. This outcome suggests that continual FMS may be necessary to maintain improved inspiratory and expiratory functions.…”
Section: Discussionsupporting
confidence: 92%
“…Researchers have also shown that hybrid exercise training (FES-leg cycling combined with arm ergometry) may elicit greater changes in peak work rates and VO 2 peak/VO 2 max than FES-leg cycling exercise alone 44,45 . Moreover, it appears that the physiological adaptations to combined FES-leg cycling and arm ergometry training are maintained partially following 8 weeks of detraining 46 . Other interventions (Table 3) that make use of hybrid FES training have also been shown to improve the exercise capacity and cardiovascular health status in SCI.…”
Section: Functional Electrical Stimulation (Fes)mentioning
confidence: 99%
“…Warburton et al 6 identified six pre-post studies that examined the effects of hybrid (FES-LCE + arm) training on cardiovascular fitness in persons with SCI, not specifically tetraplegia. [60][61][62][63][64][65] Warburton and colleagues summarized the strength of the scientific evidence for health benefits of hybrid exercise reporting level 4 evidence that hybrid exercise increases peak power output and VO 2 , and improves exercise cardiac function in those with SCI, including those with tetraplegia. [60][61][62][63][64][65] Additionally, they found level 2 evidence that FES gait training increases peak metabolic and cardiorespiratory responses in tetraplegia.…”
Section: Conducted With Eight Tetraplegicmentioning
confidence: 99%
“…[60][61][62][63][64][65] Warburton and colleagues summarized the strength of the scientific evidence for health benefits of hybrid exercise reporting level 4 evidence that hybrid exercise increases peak power output and VO 2 , and improves exercise cardiac function in those with SCI, including those with tetraplegia. [60][61][62][63][64][65] Additionally, they found level 2 evidence that FES gait training increases peak metabolic and cardiorespiratory responses in tetraplegia. 64 Metabolic and risk factors SCI Glucose homeostasis in SCI Warburton et al 6 summarized the strength of the scientific evidence for metabolic and cardiovascular benefits of hybrid exercise reporting that a minimum of 30 min of exercise 3 times per week can achieve health benefits.…”
Section: Conducted With Eight Tetraplegicmentioning
confidence: 99%